Using the two type diseases Branching Process resulted by Chemical weapon - Bestun Merza Abdul-Kareem; Drakhshan Jalal Hassan (Zanco Journal of Humanity Sciences)
In this study we have dealt with the number of child’s who are exposed the (eye, respiratory or both) diseases in the families whose at least one of their parents have the same diseases, which has caused by Chemical hit in Kurdistan of Iraq in 1988.